Do Members of Disadvantaged Groups Explain Group Status With Group Stereotypes? - Degner, Juliane; Floether, Joelle-Cathrin; Essien, Iniobong (Frontiers in Psychology, 2021)
Recent research on group attitudes in members of disadvantaged groups has provided evidence that group evaluations closely align with societal stigma, reflecting outgroup favoritism in members of those groups that are most strongly stigmatized (e.g., Essien, Calanchini, & Degner, 2021). While outgroup favoritism is clearly evident among some groups, there is still debate about the psychological mechanisms underlying outgroup favoritism (e.g., Jost, 2020; Owuamalam et al., 2018a). The current research focuses on a less intensively examined aspect of outgroup favoritism, namely the use of status-legitimizing group stereotypes. We present data from members of four disadvantaged groups (i.e., persons who self-categorize as gay or lesbian, n = 205; Black or African American, n = 209; overweight n = 200, or are aged 60-75 years n = 205), who reported the perceived status of their ingroup as well and a comparison majority outgroup and provided explanations of their status perceptions. Contrary to assumptions from System Justification Theory (SJT, Jost, 2020), participants rarely explained perceived group status differences with group stereotypes, whereas they frequently explained ingroup disadvantage with perceived stigmatization and/or systemic reasons. Further exploratory analyses indicated that participants’ status explanations were related to measures of intergroup attitudes, ideological beliefs, stigma consciousness, and experienced discrimination. Our results highlight the need to develop a better understanding whether, under which circumstances, and with which consequences members of disadvantaged groups use group stereotypes as attributions of ingroup status and status differences.